Research on the correlation between Chinaʼs scientific research, technology innovation and economic development - Korotkevich, Aleksei I.; Xiaoyun, Xu (Journal of the Belarusian State University. Economics, 2020)
The purpose is to study the relationship between China’s scientific research investment, technological innovation and economic development in the past 20 years. This article uses empirical research to sequentially analyze the time series using unit root test, cointegration test, and Bayesian network graph model analysis. The research results show that there is a long-term balanced cointegration relationship between scientific research investment, technological innovation and economic development.
Keywords: technological innovation; research investment; economic development; cointegration test; Bayesian network probability graph